Ethnomathematics: Exploration of Mathematical Elements in Oklik Music Art - Novianti, Dwi Erna; Zaenuri, Zaenuri; Mariani, Scolastika (FKIP Universitas Lampung, 2023)
Ethnomathematics: Exploration of Mathematical Elements in Oklik Music Art. Objectives: Exploring mathematical elements of Oklik as a cultures in Bojonegoro, East Java, Indonesia can be carried out in mathematics learning. This study aims to investigate the mathematical elements in it. Methods: Qualitative data analysis is implemented in this study by presenting and interpreting data which is related to mathematical elements. It includes stroke and note patterns that are produced from each instrument and combinations of it. Findings : Exploring mathematical elements viewed from types of instruments will produce different tones when it is combined well. When it is connected with musical solmization, it also produces different tones. Conclusion: Results of combinations create 32.760 tones that are produced in the notation and various strokes based on 15 combinations of instruments. Meanwhile, the solmization tones which are consisted of 12 tones; it produces 20.736 tones that can be utilized Keywords: oklik, combination of instruments, mathematical elementsDOI: http://dx.doi.org/10.23960/jpp.v13.i3.202325